Optimizing treatment efficacy and fertility preservation in patients undergoing hematopoietic stem cell transplantation: A narrative review of ovarian shielding with total‐body irradiation or treosulfan‐based conditioning regimens - Yuji Tanaka; Tetsuro Hanada; Tsukuru Amano; Akimasa Takahashi; Mari Deguchi; Hiroyuki Yamanaka; Shunichiro Tsuji; Takashi Murakami (Reproductive Medicine and Biology)
Abstract Background Pediatric and adolescent/young adult (AYA) patients with hematologic malignancies often require hematopoietic stem cell transplantation (HSCT) using conditioning regimens that pose high risks for gonadal toxicity. Traditional protocols, including total body irradiation (TBI) and busulfan‐based regimens, can impair fertility. This review explores the potential of gonadal shielding during TBI and treosulfan‐based conditioning as strategies to optimize treatment efficacy while preserving fertility. Methods A PubMed search up to February 2025 was performed for English, peer‐reviewed articles on hematologic malignancies, HSCT, shielding, and treosulfan. Studies on oncologic outcomes and fertility in pediatric and AYA patients were included. Main Findings Ovarian shielding during myeloablative conditioning with TBI effectively reduces ovarian radiation exposure, resulting in improved menstrual recovery and hormone profiles. A treosulfan‐based regimen demonstrated higher antitumor activity than a reduced‐intensity busulfan‐based regimen in randomized controlled trials. In a retrospective analysis, the treosulfan‐based regimen exhibited lower gonadal toxicity than the busulfan‐based regimen, although careful attention must be paid to dosing settings of the regimens. Conclusion Ovarian shielding during TBI and a treosulfan‐based regimen hold the potential to preserve the reproductive capacity of patients undergoing HSCT. Future clinical studies that appropriately assess both oncological outcomes and fertility are needed to validate these findings.